2008
DOI: 10.1029/2008wr006968
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistivity imaging of the architecture of substream sediments

Abstract: [1] The modeling of fluvial systems is constrained by a lack of spatial information about the continuity and structure of streambed sediments. There are few methods for noninvasive characterization of streambeds. Invasive methods using wells and cores fail to provide detailed spatial information on the prevailing architecture and its continuity. Geophysical techniques play a pivotal role in providing spatial information on subsurface properties and processes across many other environments, and we have applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…A reliable estimation of the contact between the sediments and the bedrock is thus crucial for exploring the volume of sediment in river bottoms. By using nondestructive geophysical investigation techniques, such as the two-dimensional (2D) electrical resistivity imaging (ERI) method, we can quantify the magnitude and variability of sediment covering bedrock faster, cheaper, and over a broader area than drilling a well or digging a trench (Hauck et al, 2003;Crook et al, 2008). The 2D ERI method has been a powerful technique to investigate shallow subsurface electrical structures in various environments (Cheng, 2000;Yang et al, 2002;Hauck et al, 2003;Sass, 2007;Cheng et al, 2008;Crook et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A reliable estimation of the contact between the sediments and the bedrock is thus crucial for exploring the volume of sediment in river bottoms. By using nondestructive geophysical investigation techniques, such as the two-dimensional (2D) electrical resistivity imaging (ERI) method, we can quantify the magnitude and variability of sediment covering bedrock faster, cheaper, and over a broader area than drilling a well or digging a trench (Hauck et al, 2003;Crook et al, 2008). The 2D ERI method has been a powerful technique to investigate shallow subsurface electrical structures in various environments (Cheng, 2000;Yang et al, 2002;Hauck et al, 2003;Sass, 2007;Cheng et al, 2008;Crook et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…ERI has been used to map floodplain fluvial sediments (Baines et al, 2002;Bersezio et al, 2007;Crook et al, 2008;Tye et al, 2011;, to detect gravel for commercial gravel prospecting (Auton, 1992;Beresnev et al, 2002), for geologic investigation of glacial deposits (Smith and Sjogren, 2006), for mapping buried paleochannels (Gourry et al, 2003;Green et al, 2005), and for imaging hyporheic zone solute transport (Ward et al, 2010;Menichino et al, 2012). Anterrieu et al (2010) found that two-dimensional ER profiles of a mining waste-rock pile correlated well with a model created from independently acquired data including cores, particle size distributions, and other geophysical surveys.…”
Section: Introductionmentioning
confidence: 99%
“…The inversion adjusts a finite difference or finite element model in an iterative process [11][12][13][14] by comparing the measured apparent resistivity versus the calculated resistivity from the inverted model. The use of ERT profiles and additional data from the subsurface, such as drilling reports and borehole loggings, makes it possible to estimate the thickness, depth, and morphology of different units of the subsurface [6,7,15].…”
Section: Introductionmentioning
confidence: 99%